A study on 1070 non-fatal suicidal behaviour in Portugal: a socio-demografic and clinical profile - Saraiva, Carlos Manuel Braz (2013)
After 20-years experience, these findings increased our knowledge concerning the suicidal process and coping with patient suicide.